2017
DOI: 10.1111/1751-2980.12490
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic acute pancreatitis in emergency department: Typical clinical features and genetic variants

Abstract: OBJECTIVE:To investigate the clinical characteristics of patients with hypertriglyceridemic acute pancreatitis (HTGAP), and the molecular foundation contributing to hypertriglyceridemia in such patients. METHODS:Clinical data from 329 patients with acute pancreatitis (AP) were analyzed. The patients were divided into the HTGAP group, with fasting serum triglyceride (TG) levels ≥500 mg/dL (5.65 mmol/L), and the non-HTGAP (NHTGAP) group. Targeted next-generation sequencing was applied to 11 HTGAP patients to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The classification of the pancreatitis based on the severity was as follows . MAP was defined as AP without local or systemic complications or organ failure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification of the pancreatitis based on the severity was as follows . MAP was defined as AP without local or systemic complications or organ failure.…”
Section: Methodsmentioning
confidence: 99%
“…Biliary AP was diagnosed if cholelithiasis was identified by ultrasonography, plain or contrast‐enhanced CT, MRI or MRCP. Alcohol‐related AP was defined as previously described . Hypertriglycemic AP was diagnosed when the following criteria were met: (i) triglyceride (TG) ≥11.3 mmol/L; or (ii) TG ≥5.65 mmol/L with visible chylomicronemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the prevalence and characteristics of serum triglyceride-related gene variants in adult Japanese patients with severe hypertriglyceridemia. Forty-nine genes reported to be associated with hypertriglyceridemia, including LPL, APOC2, GPIHBP1, APOA5, and LMF1, were analyzed by next-generation sequencing (NGS) 3,[6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is a frequent inflammatory disease of the pancreas with multiple causes, among which hypertriglyceridemia is the third most common and accounts for up to approximately 10% of all cases (1). Clinical studies have reported that SAP patients with HTG and obesity suffer a more severe clinical course and complications, including aggravating systemic inflammatory response,multiple organ failure, infection and high mortality (2)(3)(4). Animal experiments have also provided evidence that HTG with SAP could exacerbate oedema and necrosis of the pancreas (5).…”
Section: Introductionmentioning
confidence: 99%